Flood Disaster Management On The COVID-19 Pandemic In Sekadau Regency West Kalimantan Province - Ramadhan Pancasilawan; Herijanto Bekti; Muhammad Fedryansyah; Irfan Mauluddin (Aliansi, 2022)
Disaster management began as an emergency response to natural disasters, in the  administration of the government's emergency management program there is disaster  management. Disaster management describes the initiation of efforts to mitigate, prepare to  respond, and recover from disasters. The flood disaster management was hampered in the  management of emergency response due non-natural disasters to deal with flood natural  disasters during the pandemic COVID-19. This study will discuss in more depth how the flood  disaster management that occurred in Sekadau Regency, West Kalimantan Province during the  COVID-19 pandemic was carried out by the Sekadau Regency Regional Disaster Management  Agency. This research use descriptive qualitative approach. In collecting data, this research  uses observation, interviews, literature study, and internet searching. Data collection in this  study was carried out with existing studying literature. The author uses a model collaborative  capacities in disaster management Allen (2011), namely: Purpose, Structure, Communication,  Resources. The emergency management has a weakness, namely the loss of the community's  role in the expertise to handle flood natural disasters. The flood disaster that occurred in  Sekadau Regency, West Kalimantan Province was caused by high intensity rainfall and the  overflowing of the Kapuas River which triggered a flood disaster.